Elbow and Forearm - Simon, M.; Lutter, Christoph; Schöffl, Volker (Springer International Publishing, 2022)
Injuries in the area of the elbow represent the fourth most common entity in climbing, after finger, shoulder, and hand injuries (e.g., lateral and medial epicondylitis humeri, brachialis, biceps, and triceps muscle tendinopathies). There are also more rare injuries, such as distal biceps tendon rupture and other pathologies, which can be difficult to diagnose, such as functional compartment syndromes of the forearm or traumatic vascular and muscle injuries. Anamnesis, clinical examination, sonography, X-ray, and MRI are the basic pillars of diagnosis. In case operative therapy is required, current studies show a very good postoperative result with an often, complete restoration of the climber’s functional and sport-specific performance capacity.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Biceps tendon rupture; Compartment syndrome of the forearm; Elbow; Epicondylitis; Tendinopathies